Research Trends on the Utilization of Industrial and Domestic Waste for Sustainable Pavement Materials - Permatasari, Reby Indah (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The increase in industrial activities and urbanization has led to higher amounts of waste such as fly ash, slag, plastic waste, and construction debris, which may cause environmental problems. The utilization of these wastes in pavement construction offers a sustainable solution to reduce waste accumulation and the use of natural resources. Objective: This article aims to analyze research trends on the utilization of industrial and domestic waste as sustainable pavement materials. Method: This study employed a literature review of 15 scientific articles retrieved from Google Scholar, analyzed based on waste type, pavement type, technical performance parameters, and environmental aspects. Results and Discussion: The findings show that fly ash is the most studied waste material, followed by slag, plastic waste, and recycled concrete aggregate (RCA). Most studies focus on flexible asphalt pavements using parameters such as Marshall Stability, compressive strength, and CBR. Proper waste incorporation improves technical performance while reducing natural aggregate consumption and waste disposal. Conclusion: The use of industrial and domestic waste in pavement construction has strong potential to support sustainable infrastructure development, although more integrated technical and environmental evaluation is still needed.